2022
DOI: 10.1002/suco.202100662
|View full text |Cite
|
Sign up to set email alerts
|

Finite element numerical simulation of a cable‐stayed bridge construction through the progressive cantilever method

Abstract: Cable-stayed structures have become popular worldwide as one of the main alternatives for bridge designs with spans from 200 to 1000 m. Due to the dimensions of the structural elements that typically compose such bridges and their nonlinear structural behavior, it is usually employed in the designing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…There are some studies of numerical simulation of concrete performance by finite element method (FEM) [34][35][36] and XFEM. 37,38 The essential idea of XFEM is to characterize the discontinuous displacement field (crack and crack growth) independent of the finite element mesh by adding enrichment functions to conventional FEM.…”
Section: Extended Finite Element Methodsmentioning
confidence: 99%
“…There are some studies of numerical simulation of concrete performance by finite element method (FEM) [34][35][36] and XFEM. 37,38 The essential idea of XFEM is to characterize the discontinuous displacement field (crack and crack growth) independent of the finite element mesh by adding enrichment functions to conventional FEM.…”
Section: Extended Finite Element Methodsmentioning
confidence: 99%
“…Case studies have shown the beneficial influence of numerical research on concrete bridges, leading to safer, more resilient, and long-lasting structures [12]. Researchers have conducted numerous case studies to solve a wide range of problems, such as a novel non-linear analysis model created to examine the effects of creep and shrinkage on long-span prestressed concrete box girder bridges [13], the construction of a prestressed concrete cable-stayed bridge by employing the progressive cantilever method in FEM [14], a shell model for the load-carrying capacity of prestressed concrete bridges under shear and torsion [15], and a new FEM for analyzing the structural behavior of fiber-reinforced polymer (FRP)-strengthened steel-reinforced concrete (RC) beams under cyclic loading using FEM [16].…”
Section: Introductionmentioning
confidence: 99%